Hungarica digitalia: Hongaarse bronnen in Nederlandse digitale collecties van archieven, musea en bibliotheken - Teszelszky, Kees (Acta Neerlandica, 2022)
We live in a Golden Age for doing research on Dutch-Hungarian relations, as so many Dutch archives, museums and libraries digitise their collections and new research environments became available. The author describes in this article shortly the new trends in digital humanities and introduces recently digitised or born digital material and new available digital collections with Hungarian sources on the history of Dutch-Hungarian relations or at the Utrecht City Archives, The Rijksmuseum Amsterdam, the Amsterdam City Archives, the digital library Delpher of KB – National Library of the Netherlands and the Dutch web archive of the same library.